Dynamika wzajemnych relacji między Unią Europejską a Chińską Republiką Ludową na początku XXI wieku - Żódź-Kuźnia, Katarzyna; Wiśniewski, Janusz (Przegląd Politologiczny, 2018)
On account of their potential, and the growing international influence of the EU and the People’s Republic of China, the mutual relations of both parties conducted at the level of a complex strategic partnership are a priority for both of them. The scope of the said partnership is consistently expanding and includes new dimensions and instruments of cooperation. Modern re- lations between the EU and China go far beyond the economic issues which, nevertheless, remain the main part of bilateral relations. Still, both parties have noted that they have common geopolitical interests and they are in agreement that political dialogue should deepen and expand. The common interests in EU-Chinese relations are accompanied by a number of divergent ones. The main discrepancy concerns political issues (lack of democratic standards, violation of freedom and civil rights, and the EU’s embargo on weapons) as well as economic ones (the free market status of the Chinese economy and the violation of intellectual property laws by China). From the point of view of the European Union, particular significance in relations with China should be given to the coordination and cohesion of national policies conducted by indi- vidual Member States and to the practical application of commonly agreed priorities. Only an EU speaking with a single voice can be a credible and significant partner for China, which after the years of being marginalized is returning to the circle of great powers of the modern world.